2004
DOI: 10.1111/j.0022-202x.2004.22305.x
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis-Like Cutaneous Inflammation in Mice Lacking Interleukin-1 Receptor Antagonist

Abstract: Interleukin-1 receptor antagonist-deficient (Il1rn-/-) BALB/c mice developed inflammation localized to the skin of the ear pinna in 64% of the cases examined. Histopathologically, the disease had many features resembling human psoriasis, suggesting that it might be a useful disease model. The epidermis became thickened and hypertrophic, and expressed the immature keratin, K6, throughout. The stratum corneum showed parakeratotsis. Large epidermal projections formed into a grossly thickened dermis and both tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 16 publications
2
72
0
3
Order By: Relevance
“…1D). These histological features of the Il1rn 2/2 epidermis resembled those seen in human psoriasis vulgaris, as reported previously (21,22).…”
Section: Cutaneous Inflammation Develops In Il1rnsupporting
confidence: 87%
See 2 more Smart Citations
“…1D). These histological features of the Il1rn 2/2 epidermis resembled those seen in human psoriasis vulgaris, as reported previously (21,22).…”
Section: Cutaneous Inflammation Develops In Il1rnsupporting
confidence: 87%
“…Given that arthritis and aortitis, which develop in the same Il1rn 2/2 animals, result from autoimmune mechanisms that are strictly dependent on T cells, the reason underlying the independence of psoriasiform skin lesion from autoimmunity against skin Ags is not clear; it is possible that keratinocytes are efficient producers of inflammatory cytokines and chemokines upon stimulation with IL-1, such that the action of these inflammatory mediators is sufficient to induce inflammation without the involvement of the immune system. We do not exclude the possibility completely, however, that immune responses function in the elicitation phase, because abundant dendritic cells and activated T cells are detected in psoriasiform lesions of affected Il1rn 2/2 mice (21,22). Consistent with this possibility, we observed development of dermatitis in Il1rn 2/2 BMC-transferred WT mice at the late stage, although the incidence was low (Table IV).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The role of IL-1R1 signaling has received renewed focus in the context of psoriasiform inflammation as a consequence of observations implicating the IL-23/IL-17 axis as a central mediator of disease (19). Interestingly mice deficient in IL-1R1 antagonist, an endogenous suppressor of IL-1R1 signaling, develop spontaneous autoimmune inflammation in the skin (38). This phenotype is strikingly similar to common manifestations of human psoriasis, with marked acantosis, hyperkeratosis, and a nucleated cell infiltrate.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that transgenic mice overexpressing IL-1␣ in basal keratinocytes developed focal inflammatory skin lesions, 43 whereas others have reported psoriasiform lesions on BALB/c IL-1 receptor antagonist knockout mice. 44 The strong induction by IL-1␣ of antimicrobial molecules is of particular interest. S100A7 has been shown recently to exhibit potent antimicrobial properties, particularly against E. coli.…”
Section: Discussionmentioning
confidence: 99%